2021
DOI: 10.1186/s13048-020-00763-z
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of recombinant human lactoferrin on the premature ovarian failure in rats after cyclophosphamide treatments

Abstract: This study investigated the effect of recombinant human lactoferrin (rhLF) on the premature ovarian failure (POF) of rats. After cyclophosphamide treatments, the POF rats were divided into the following groups: normal control group (NC), low-dose group (LD), medium-dose group (MD) and high-dose group (HD) of rhLF. After drug administrations, the ovarian indexes and hormonal levels were detected. After follicle number count, the proliferation and apoptosis were analyzed with the expressions of genes related wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Many studies have shown that CTX causes ovarian dysfunction including accelerated loss of ovarian reserve, folliculogenesis dysregulation, and steroid disorder. 3,4,16 We found that the serum FSH and LH levels were significantly increased and the E2 and P levels were decreased in rats treated with CTX. The number of atretic follicles was increased by the CTX treatment; conversely, the decreased number of primordial, primary, and secondary follicles resulted in a decreased number of total follicles, which was in line with a previous report.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Many studies have shown that CTX causes ovarian dysfunction including accelerated loss of ovarian reserve, folliculogenesis dysregulation, and steroid disorder. 3,4,16 We found that the serum FSH and LH levels were significantly increased and the E2 and P levels were decreased in rats treated with CTX. The number of atretic follicles was increased by the CTX treatment; conversely, the decreased number of primordial, primary, and secondary follicles resulted in a decreased number of total follicles, which was in line with a previous report.…”
Section: Discussionmentioning
confidence: 76%
“…The CTX-induced POF rats model was established according to the previous studies. 16,17 The rats of the POF, MT10, and MT20 groups were intraperitoneally injected with 50 mg/kg of CTX on the first day and then 8 mg/kg for 15 consecutive days, while the control group was injected with 0.9% saline instead of CTX. The rats of the MT10 and MT20 groups were injected with melatonin (Sigma, St. Louis, MO, USA) at 10, or 20 mg/kg body weight (i.p.…”
Section: Methodsmentioning
confidence: 99%
“…55 In addition, S. B. Li et al reported that the oral administration of recombinant human lactoferrin alleviated cyclophosphamide-induced POF symptoms by increasing the hormone levels of E2 and AMH and inhibiting apoptosis. 56 It is speculated that the potential regulatory effects of proteins and protein derivatives on sex hormones may be related to their amino acid composition. The total peptide content of SCP reached 808.24 mg g −1 , and the 6 amino acids with the highest content were Gly (24.35%) > Glu (15.45%) > Ala (11.45%) > Pro (10.28%) > Arg (7.44%) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AMH plays an important role in follicular development and is an important marker of follicular health. 53 56 It is speculated that the potential regulatory effects of proteins and protein derivatives on sex hormones may be related to their amino acid composition. The total peptide content of SCP reached 808.24 mg g −1 , and the 6 amino acids with the highest content were Gly (24.35%) > Glu (15.45%) > Ala (11.45%) > Pro (10.28%) > Arg (7.44%) (data not shown).…”
Section: Papermentioning
confidence: 99%
“…Therefore, antioxidant administration would be helpful to alleviate oxidative stress for these patients. Lactoferrin (LF) is a well-known antioxidant [29]. LF incorporated titanium disc improves antibacterial and osteoinductive ability of dental implant [30].…”
Section: Discussionmentioning
confidence: 99%